Expression of Heme Oxygenase-1 in the Peripheral Blood Mononuclear Cells from Asthmatic Patients - 莫碧文 张珍祥 徐永健 熊维宁 刘先胜 甄国华 (Journal of Huazhong University of Science and Technology. Medical sciences, 2005)
Summary： To explore the expression of heme oxygenase-1 （HO-1） in the peripheral blood mononuclear cells （PBMCs） and its relationship with pulmonary ventilation function in asthmatic patients, 18 asthmatic patients and 18 healthy subjects were selected. HO-1 protein and mRNA levels in PBMCs were measured by immunohistochemical staining and reverse transcription-polymerase chain reaction （RT-PCR）, respectively. Blood carbon monoxide Hb （COHb）, serum total IgE and pulmonary ventilatory function were observed. Our results showed that the percentage of cells positive for immunohistochemical staining of HO-1 were significantly higher in asthmatic patients （41.72±7.44） % than that in with healthy subjects （10.45±4.36）% （P〈0.001） and the optical density of PBMC HO-1 mRNA was higher in asthmatic patients （26.05±4. 14） than that in healthy subjects （10.82±4.26） （P〈0.001）. The relation analysis showed that PBMC HO-1 protein and mRNA levels had significantly negative relation with FEV, %, PEFR, MEFR50 , respectively （r=-0.51-0.89, P〈0.05-0. 001, respectively） and a positive relation with COHb and serum total IgE （r=0.48-0. 85, 0.05-0. 001, respectively）. It is concluded that the expression of PBMC HO-1 protein and mRNA increased significantly in asthmatic patients, and HO-1 may play a significant role in the pathogenesis of asthma. The expression of HO-1 may bear a relation with severity of asthma.